2017
DOI: 10.1111/acem.13347
|View full text |Cite
|
Sign up to set email alerts
|

Patient‐level Factors and the Quality of Care Delivered in Pediatric Emergency Departments

Abstract: We found that quality of ED care delivered to children among a cohort of 12 EDs participating in the PECARN was high and did not differ by patient age, sex, race/ethnicity, and payment source, but did vary by the presenting chief complaint.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…Besides, it reduced the waiting period between the hospital admission and examination by a physician, along with a length of a hospital stay. Moreover, the proportion of patients who left the waiting room without doctor's examination declined by 50%, which improved their safety [3].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, it reduced the waiting period between the hospital admission and examination by a physician, along with a length of a hospital stay. Moreover, the proportion of patients who left the waiting room without doctor's examination declined by 50%, which improved their safety [3].…”
Section: Discussionmentioning
confidence: 99%
“…This situation is explained by the lack of clinical guidelines developed for management of emergency pathologies at the preclinical stage [2]. The number of patients admitted to emergency departments cannot be predicted with great precision; and only a fraction of those suffers from lifethreatening diseases or conditions requiring urgent care [3], and not all patients are in need of immediate medical care. Therefore, patients with severe pathologies and life-threatening injuries should be identified within minutes of their admission to emergency departments [4].…”
Section: Introductionmentioning
confidence: 99%
“…The PECARN has developed and validated instruments to evaluate the quality of care delivery in pediatric care by using implicit review methods that can be used for diverse groups of patients . A recent study used this implicit review methods tool to look at patient‐level factors and the quality of care in 12 PECARN EDs and found that some chief complaint categories were associated with significantly lower than average quality of care, including fever (–0.65 points in quality, 95% CI = –1.24 to –0.06) and upper respiratory symptoms (–0.68 points in quality, 95% CI = –1.30 to –0.07) . The concern with current measures related to pediatric emergency care is the lack of a systematic and comprehensive approach.…”
Section: Conceptual Framework and Creation Of The Research Agendamentioning
confidence: 99%
“…The number of patients visiting to emergency departments cannot be accurately predicted, and only some of them have life‐threatening diseases or require urgent treatment (Marcin et al., 2018), and but not all patients require immediate treatment (Pivina et al., 2021). Therefore, the triage process is essential to discriminate the priority of emergency patients visiting the emergency department (National Emergency Nurses Association, 2019).…”
Section: Introductionmentioning
confidence: 99%